Persistence of HIV transmission clusters among people who inject drugs. (15th November 2020) - Rose, Rebecca; Cross, Sissy; Lamers, Susanna L.; Astemborski, Jacquie; Kirk, Greg D.; Mehta, Shruti H.; Sievers, Matthew; Martens, Craig; Bruno, Daniel; Redd, Andrew D.; Laeyendecker, Oliver
Abstract : Objective: We investigated the duration of HIV transmission clusters. Design: Fifty-four individuals newly infected at enrollment in the ALIVE cohort were included, all of whom had sequences at an intake visit (T1) and from a second (T2) and/or a third (T3) follow-up visit, median 2.9 and 5.4 years later, respectively. Methods: Sequences were generated using the 454 DNA sequencing platform for portions of HIV pol and env (HXB2 positions 2717–3230; 7941–8264). Genetic distances were calculated using tn93 and sequences were clustered over a range of thresholds (1--5%) using HIV-TRACE. Analyses were performed separately for individuals with pol sequences for T1 + T2 ( n  = 40, 'Set 1') and T1 + T3 ( n  = 25; 'Set 2'), and env sequences for T1 + T2 ( n  = 47, 'Set 1'), and T1 + T3 ( n  = 30; 'Set 2'). Results: For pol, with one exception, a single cluster contained more than 75% of samples at all thresholds, and cluster composition was at least 90% concordant between time points/thresholds. For env, two major clusters (A and B) were observed at T1 and T2/T3, although cluster composition concordance between time points/thresholds was low (<60%) at lower thresholds for both sets 1 and 2. In addition, several individuals were included in clusters at T2/T3, although not at T1. Conclusion: Caution should be used in applying a single threshold in population studies where seroconversion dates are unknown. However, the retention of some clusters even after 5 + years is evidence for the robustness of the clustering approach in general. Abstract : Supplemental Digital Content is available in the text